Antioxidant and Antibacterial Activities of Patin Fish Skin Gelatin Edible Coating with Carrageenan and Red Ginger Essential Oil - Nurdiani, Rahmi; Ningsih, Omega Tantia; Fauzi, Ahmad Adnan; Yasmin, Putri; Puspitasari, Dwi Anggraini; Astuti, Retno Tri; Kusuma, Bayu (Universitas Gadjah Mada, 2025)
Fresh fish are highly perishable due to their high moisture content, requiring proper handling to extend their shelf life. Edible coatings using fish-derived gelatin offer a halal and eco-friendly alternative. This study aimed to enhance the antioxidant and antibacterial activities of patin fish skin gelatin by combining it with carrageenan and red ginger essential oils. This study involved gelatin and edible coating production, followed by testing for antioxidant and antibacterial activities against S. aureus and E. coli. Formula optimization was performed using Response Surface Methodology (RSM) via Design Expert V12, with the results verified through a Paired T-Test in Minitab 19. The addition of carrageenan and red ginger essential oils significantly affected the inhibition percentage and antibacterial activity. The optimal formula included 0.5 g carrageenan and 1.5 mL red ginger essential oil. The verification steps showed alignment with predictions for Staphylococcus aureus but not for Escherichia coli.